ULTRASOUND AND ORGANIC ACIDS Salmonella enterica Enteritidis AND Escherichia coli FROM PEARS SURFACES - de São José, Jackline Freitas Brilhante; de Medeiros, Hiasmyne Silva; de Andrade, Nélio José; Bernardes, Patrícia Campos (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
The aim of this study was to evaluate the eff ectiveness of ultrasound treatment combined with organic acids in the decontamination step for pears processing. The adhesion process by Salmonella enterica serovar Enteritidis and Escherichia coli on pears surfaces was evaluated. In addition, the effi ciency of ultrasound and organic acids to remove bacteria from the pears surfaces was analyzed. The average roughness (Ra) of the pears was 11.85 ± 3.53 nm. The processes of S. Enteritidis and E. coli adherence are thermodynamically unfavorable for surface studied (ΔGadhesion >0) but good adhesion occurred. These results suggest that the adhesion observed in this experiment is a multifactorial process. The number of bacteria on pears slices was 6.65 e 7.00 log CFU/cm2 for E. coli and S. enterica Enteritidis, respectively. All of the treatments removed more than 0.94 log CFU/cm2. Of the treatments evaluated, a higher removal of pathogens was observed after use of 1% lactic acid, which reduced the E. coli and Salmonella contamination by 1.95 and 2.55 log CFU/cm2, respectively. The results showed that it is possible to replace chlorinated compounds, which are frequently used to sanitize fruits and vegetables. Ultrasound can improve bacterial reduction of acetic acid treatment. These indicates that ultrasound can contribute to microbial safety of fresh products when applied in combination with chemical compounds.